Welfare - Barry, Norman P. (Open University Press, 1999)
The idea of welfare in political thought. Utilitarianism and the origins of welfare philosophy. Anti-individualism. Libaral political economy and the ethics of welfare. Justice, equality and welfare. Welfare, the welfare state and politics. Welfare.